Mouse IPK: A Powerful Tool to Partially Characterize Renal Reperfusion and Preservation Injury - Lindell, Susanne L. (2011)
MAIN PROBLEM: The molecular basis of renal preservation injury is not well understood. Since mouse kidney transplantation models are not useful in this setting, a mouse Isolated Perfused Kidney (IPK) model was developed to take advantage of mouse genetic design capabilities for testing complex biological hypothesis regarding mechanisms of preservation injury in transplanted kidneys. METHODS: Mouse kidneys were recovered, preserved, and reperfused in-vitro with an acellular physiological crystalloid buffer containing hypo-physiological oncotic pressure. Outcome variables were measured to predict preservation injury. These included perfusate flow, vascular resistance, VO(2), urine output, GFR, proteinuria, LDH release, and edema. The model was tested by subjecting mouse kidneys to cold storage in University of Wisconsin (UW) solution for 24, 48, or 72 hours (time-dependent preservation injury), cold storage in Euro-Collins Solution (solution dependent preservation injury), and exposure to prior warm ischemia (DCD dependent preservation injury). RESULTS: The model accurately predicted the qualitative and quantitative changes in the readouts based on known responses to preservation injury in kidney transplants in large animals and humans. CONCLUSION: The mouse IPK accurately predicts many of the variables associated with renal organ preservation injury in the very early phases of reperfusion and may provide an attractive model for studying the molecular basis of renal preservation injury.